2015
DOI: 10.1016/j.celrep.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

MERIT40 Is an Akt Substrate that Promotes Resolution of DNA Damage Induced by Chemotherapy

Abstract: Summary Resistance to cytotoxic chemotherapy drugs, including doxorubicin, is a significant obstacle to the effective treatment of breast cancer. Here, we have identified a mechanism by which the PI3K/Akt pathway mediates resistance to doxorubicin. In addition to inducing DNA damage, doxorubicin triggers sustained activation of Akt signaling in breast cancer cells. We show that Akt contributes to chemotherapy resistance such that PI3K or Akt inhibitors sensitize cells to doxorubicin. We identify MERIT40, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 31 publications
7
50
0
Order By: Relevance
“…Cell viability was assessed using sulforhodamine B assay as previously described (18). Briefly, adherent cells were fixed with 12.5% (w/v) trichloroacetic acid for 1 hour at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was assessed using sulforhodamine B assay as previously described (18). Briefly, adherent cells were fixed with 12.5% (w/v) trichloroacetic acid for 1 hour at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…These included, for example, XLF (XRCC4-like factor) and UBE2S (ubiquitin-conjugating enzyme E2 S) as Akt target proteins connected to NHEJ, as well as MERIT40 (mediator of Rap80 Interactions and Targeting 40 kDa), and EMSY (BRCA2-interacting transcriptional repressor) with suggested functions in HRR [9,10,11,14,15]; reviewed by Reference [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Jiang and colleagues [78] demonstrated that end resection and HR are reduced after ICLs damage in MERIT40-null cells. Another study suggested that MERIT40 might be a drug target because MERIT40 was phosphorylated by Akt, which is activated by cancer drug doxorubicin [80]. Phosphorylated MERIT40 increases the accumulation of BRCA1-A complex at sites of DNA damage induced by doxorubicin, which is a cytotoxic chemotherapy drug.…”
Section: Merit40mentioning
confidence: 99%